Holistic Thinking in Head Mastersof the Secondary Schools in Diyala province (Journal of the College of Basic Education, 2022)
Progection of the study is to know : 1-holistic thinking level in head masters of the secondary schools according to the changes of sex and service period . by taking (165) of head masters (males and females) from Diyala education dirocterate by random methods , and by the use ofdescreptional items to do this research by uses special measure (holistic thinking).depending on Sternebrik theory for holistic thinking and from sure that the psychotic properties for this measer and extract the honest is by two methods : superficial honesty and bulding honesty , also extract consistency by two methods .also extract consistencyby two methods. Again the testis by stability coefficient (0.88) but alpha krunbach(0,78. The final measure is (41) items for measure the holistic thinking in secondary school. The stastistical treatment by use (arethmatic mean, standerd deviation, T-test for one sample, T- test for two disoriented samples, person coeficient factor, defferance analtsis, Z-test and(SPSS). The net results are: ---The secondary schools head masters enjoy in high level of holistic thinking.---Nodefferance is indicated statistically in level of holistic thinking between head masters of the secondary schools according to sex. ---NO staststical defferancein holistic thinking level among secondaryschools head masrers according to service period. --Finally there are some recommendations and suggestions.